The role of the network factor for immigrants in intercultural resilience building on the example of the Intercultural Cities Programme - Borisova , Diana (Tudásmenedzsment, 2023)
Migration is a process, which is associated with realizing cultural differences in understanding the self, relationships and the world and learning new ways of existence. Promoting multiple forms of the positive interaction creates a sense of belonging and cohesion for immigrants. In this context, “interaction" refers to the everyday processes or networking on the grounds of which migrants maintain contact with each other and with receiving societies. Therefore, a lot of cities realise policies and projects that ensure the application of equal rights for all, fight against discrimination and racism, and support constructive interaction between individuals and groups of different backgrounds, different cultures and different generations. The purpose of this research is to consider how one of these programs, namely the Intercultural Cities Programme, takes into account the network factor in its implementation and to prove how important this factor is for integrating immigrants into the host community. The hypothesis of this work is based on the idea that the using of the network factor develops intercultural resilience building. The primary method for this study is literature review. The examination of appropriate literature gives rigorous description of current situation with immigrants and cross-cultural resilience in general and within the framework of the Intercultural Cities project. Research results reflect the idea of integrating immigrants into communities with the help of network factor. The significance of this study is conditioned by providing learning cities with information about cross-cultural resilience building and making cities all over the world rethink their policies for using diversity as a stimulus to progress.